2020
DOI: 10.3390/su12104066
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Competitive and Sustainable Destination of the Future: Clusters and Predictors of Successful National-Level Destination Governance across Destination Life-Cycle

Abstract: This study advances the research and methodological approach to measuring and understanding national-level destination competitiveness, sustainability and governance, by creating a model that could be of use for both developing and developed destinations. The study gives a detailed overview of the research field of measuring destination competitiveness and sustainability. It also identifies major predictors of destination competitiveness and sustainability and thereby presents destination researchers and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 98 publications
0
32
0
1
Order By: Relevance
“…Innovation is pertinent, not only for competitiveness for tourism firms and destinations, but also for enhancing environmental protection and social benefits from the perspective of sustainable tourism [39]. The great importance of sustainability for the competitiveness of tourism destinations worldwide, and especially for developed destinations, has recently been confirmed, which should imply a change in the behaviour of destination managers in relation to sustainability [40]. Since tourism development is mainly based on the exploitation of the natural resources of destinations, the process of tourism innovation should respect the criterion of sustainable development [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovation is pertinent, not only for competitiveness for tourism firms and destinations, but also for enhancing environmental protection and social benefits from the perspective of sustainable tourism [39]. The great importance of sustainability for the competitiveness of tourism destinations worldwide, and especially for developed destinations, has recently been confirmed, which should imply a change in the behaviour of destination managers in relation to sustainability [40]. Since tourism development is mainly based on the exploitation of the natural resources of destinations, the process of tourism innovation should respect the criterion of sustainable development [41].…”
Section: Introductionmentioning
confidence: 99%
“…In the long term, the competitiveness of tourism destinations is linked to their sustainability, i.e., to the protection of natural and cultural resources that guarantee their attractiveness [42]. In fact, sustainability should play an important role, not only in promoting the long-term competitiveness of developing tourism destinations but also, and even more importantly, in the competitiveness of developed destinations [40]. The innovative propensity of a hotel or accommodation service provider, for example, depends not only on the use of technology but also on sustainable initiatives; the latter perhaps being the reason why ecotourism is becoming increasingly popular amongst people who want to connect tourism with the environment and natural settings [1].…”
Section: Introductionmentioning
confidence: 99%
“…A recent and detailed study in the field of measuring destination competitiveness and sustainability was conducted by Paunovic I. et al (2020). Through their research [45], the authors propose a new reference model with two types of destination for which they identified the major predictors of destination competitiveness and sustainability, with implications for destination planning and governance arrangements. Dwyer and Kim (2003) highlighted the importance of the internal managerial function for destination competitiveness [46].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Untuk itu, mereka merekomendasikan bahwa destinasi wisata di Italia perlu memberikan perhatian pada keseimbangan antara Input dan output. Paunović et al (2020) yang melakukan penelitian di Switzerland menemukan bahwa ada keunggulan pada dimensi sumber daya alam (natural) dan sumber daya budaya, memerlukan banyak investasi, manajemen perencanaan/ marketing strategi yang jitu, tepat sasaran untuk menjadikan destinasi lebih menarik bagi pengunjung internasional guna memperbaiki daya saing wilayah tersebut. Günlü & Küçükaltan (2017) yang mengaitkan antara daya saing destinasi wisata dan kualitas hidup penduduk lokal di Turki menemukan bahwa ada hubungan antara daya saing wisata dan kualitas hidup.…”
Section: Telaah Literaturunclassified